A survey: awareness of peoples in different sectors investing Islamic Unit Trust in Malacca / Ahmad Nazri Yusof - Yusof, Ahmad Nazri (Faculty of Business and Management, 2011)
Islamic Unit trust funds have grown with higher participation from private investors and institutions in Muslim countries for Islamic equity fund. Unit trust in Malaysia also have experienced a considerable growth over the last decade in terms of the number of funds offered and the volume of capital managed by unit trust management companies. This study is conducted to identify the awareness of people toward Islamic unit trust fund. A set of questionnaire was randomly distributed to 103 respondents in collecting the data and only 100 respondents return back the questionnaires. The questionnaire is designed to test the respondent awareness about Islamic unit trust fund. This questionnaire has distributed to peoples in Malacca. The independent variables that be used are Knowledge, advertising and lastly social influence. Likert scale is the best type that be used in most questions to determine the level of understanding how strongly agree or strongly disagree of the respondent with the statement regarding the principles. As the conclusion of this study, this report presents the results of the study related to the issue of Islamic unit trust fund.